Improved osteogenic differentiation of human induced pluripotent stem cells cultured on polyvinylidene fluoride/collagen/platelet‐rich plasma composite nanofibers. Issue 2 (27th June 2019) - Abazari, Mohammad Foad; Soleimanifar, Fatemeh; Amini Faskhodi, Mojdeh; Mansour, Reyhaneh Nassiri; Amini Mahabadi, Javad; Sadeghi, Solmaz; Hassannia, Hadi; Saburi, Ehsan; Enderami, Seyed Ehsan; Khani, Mohammad Mehdi; Zare Karizi, Shohreh
Abstract: Blood transfusion or blood products, such as plasma, have a long history in improving health, but today, platelet‐rich plasma (PRP) is used in various medical areas such as surgery, orthopedics, and rheumatology in many ways. Considering the high efficiency of tissue engineering in repairing bone defects, in this study, we investigated the combined effect of nanofibrous scaffolds in combination with PRP on the osteogenic differentiation potential of human induced pluripotent stem cells (iPSCs). Electrospinning was used for fabricating nanofibrous scaffolds by polyvinylidene fluoride/collagen (PVDF/col) with and without PRP. After scaffold characterization, the osteoinductivity of the fabricated scaffolds was studied by culturing human iPSCs under osteogenic medium. The results showed that PRP has a considerable positive effect on the biocompatibility of the PVDF/col nanofibrous scaffold when examined by protein adsorption, cell attachment, and 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assays. In addition, the results obtained from alkaline phosphatase activity and calcium content assays demonstrated that nanofibers have higher osteoinductivity while grown on PRP‐incorporated PVDF/col nanofibers. These results were also confirmed while the osteogenic differentiation of the iPSCs was more investigated by evaluating the most important bone‐related genes expression level. According to the results, it can be concluded that PVDF/col/PRP has much more osteoinductivity while compared with the PVDF/col, and it can be introduced as a promising bone bio‐implant for use in bone tissue engineering applications. Abstract : 1. Electrospun polyvinylidene fluoride/collagen (PVDF/col) nanofibers with and without platelet rich plasma (PRP) were fabricated and characterized. 2. PRP has a considerable positive effect on the biocompatibility of the PVDF/col nanofibrous scaffold when examined by protein adsorption, cell attachment and viability assay of the human induced pluripotent stem cells (iPSCs). 3. The osteoinductivity of the fabricated scaffolds was studied by culturing of human iPSCs under osteogenic medium and the results obtained from alkaline phosphatase activity, calcium content and bone related genes assays demonstrated that PRP‐incorporated nanofibers have higher osteoinductivity compared with empty nanofibers.